Microhabitat use by species of the genera Bothrops and Crotalus (Viperidae) in semi-extensive captivity - Gomes, Cristian Alexandro [UNESP]; Almeida-Santos, S. M. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2012)
Many factors influence microhabitat including climate and the occurrence of predators, prey and suitable shelters. The influence of predators in a semi-extensive breeding system is minimized due to frequent monitoring of the area. This situation enables the independent analysis of such other variables as refuges and temperature. Some specimens of the Viperidae family are kept in a semi-extensive breeding system at the Butantan Institute for display and study. These animals are widely distributed in the Atlantic Forest and Cerrado, two biomes with distinct climatic characteristics. We compared the daily activity pattern and microhabitat use of the species Bothrops jararaca and Crotalus durissus terrificus. Our main questions were whether rattlesnakes and lancehead snakes respond to habitat selection differently in similar climatic conditions and if they choose similar microhabitats. Species of the genus Bothrops were frequently found under shelters regardless of the time of day. On the other hand, snakes of the genus Crotalus were frequently found sheltered during the early morning, then migrated to sunnier areas and returned to shelters in late afternoon. © CEVAP 2012.
Keywords: Microhabitat selection; Snakes; Thermoregulation; Viperidae